Fat deposition in tropical sheep as adaptive attribute to periodic feed fluctuation - Ermias, E.; Yami, A.; Rege, J.E.O. (Wiley, 2002)
Ruminants adapt to periodic fluctuation in feed resources by accumulating fat stores during favourable periods. Thus, genetic variations, among ruminant genotypes, in the capa city to deposit fat could be exploited through breeding to improve animal productivity in traditional tropical production systems. Based on this premise, breed differences among weights of principal adipose depots and total body fat were estimated in Menz (n = 303) and Horro (n = 151) sheep of Ethiopia. Animals were kept on supplemental feeding, for about 3.5 months, until slaughter at about 17 months of age and preslaugliter live weight of 25 k . Except the combined weight of tail and rump fat (TRF) which was similar (p > 0.05) in the two reeds, weights of subcutaneous and intermuscular fat (SIF), internal fat (IF) as well as total dissected body fat (TotDF), total ether extracted body fat (TotEE) and TotFAT (TotDF plus `residual' fat, fat recovered by ether extraction from non adipose tissues) were significantly (p < 0.01) higher in the Menz. TotDF, TotEE and TotFAT were 1.91 f 0.04, 2.05 f 0.06 and 2.64 f 0.06 kg, respectively, in the Menz and 1.50 ± 0.05, 1.44 t 0.06 and 2.02 t 0.07 kg, respectively, in the Horro. Implications of breed differences in fat distribution among depots, and possible consequences of genetic improvement of some of the depots on adaptation to climatic and nutritional stresses as well as some production objectives are discussed.